Infective endocarditis secondary to Peptoniphilus Indolicus and Corynebacterium: an amalgamation - Waleed, Madeeha Subhan; Sadiq, Waleed; Alex, Milena; Pathalapati, Radhika; Ahmed, Shahzad (Acta Biomedica Atenei Parmensis, 2023)
Corynebacterium or diphtheroid’s are gram-positive aerobic, pleomorphic skin and mucosal membrane components that are not pathogenic in nature. Peptostreptococcus indolicus belongs to the Peptostreptococcus genus and is a Gram-Positive Anaerobic Cocci (GPAC). Less than one percent of endocarditis is caused by gram-positive anaerobic bacteria. We report the first case of Peptoniphilus indolicus and Corynebacterium endocarditis in a patient with native valves and a pacemaker. In time, diagnosis of a Peptoniphilus indolicus infection can lead to early management of the infection and a decreased incidence of serious complications such as embolization or abscess formation. The combination of aggressive antibiotic administration and surgical intervention can significantly decrease morbidity and mortality. This case report will highlight the importance of Peptoniphilus infective endocarditis, ultimately leading to better diagnostic strategies and management.